SOCIAL RESPONS PÅ URBANISERINGENS EPIDEMIER: Aids-oplysning i det sydlige Zambia - Mogensen, Hanne Overgaard (Tidsskriftet Antropologi, 1996)
Hanne Overgaard Mogensen: A Social Response to the Epidemics of Urbanization. AIDS Information in Southern Zambia In Southern Zambia, Tonga people associate AIDS with a locally defined disease called kahungo which is said to be caused by contact with symbolically polluted biood. Before the arrival of AIDS, kahungo was associated with TB and sexually transmitted diseases. In Africa, epidemics of TB and STDs were often related to colonization and urbanization. Similar to AIDS, they spread more rapidly than what was known in Europe, and the colonial administration tried to explain this with “problems of behaviour”, thereby ignoring the miserable conditions under which people lived. The Tongas’ association of these diseases with kahungo should be seen as a social response to new epidemics. While the Europeans talked about individual problems of adaptation to modem life, kahungo concems the collective responsibility to maintain order. Kahungo, a disease of disorderly biood, has become the symbol of the disorder of urbanization and modemization.